Sengketa Sertipikat Ganda Akibat Perbuatan Melawan Hukum - Muhammad Daffa Ariansyah; Reni Anggriani (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
Legal certainty for land ownership in the form of a certificate has been regulated in Government Regulation Number 24 of 1997 jo. Government Regulation Number 18 of 2021, but not all certificates provide legal certainty, as in civil case No. 282/PDT.G/2020/PN SMG, namely land ownership disputes, namely the existence of multiple certificates of land rights on the same plot of land. The research is to find out how legal protection is related to legal certainty for holders of proof of ownership of land rights based on Government Regulation Number 24 of 1997 jo. PP Number 18 of 2021 concerning Land Registration by disclosing facts according to the conditions and realities that exist in society. The method used is normative. Legal certainty regarding land ownership is evidenced by a certificate that has been made in accordance with applicable procedures. The inhibiting factor for the government in the land registration process so that the products issued do not cause administrative defects is the existence of socialization from the government, in this case ATR/BPN, for all processes and documents that need to be considered in the land registration process.